Technology without borders : case studies of successful technology transfer - International Energy Agency (Paris : IEA Publications, 2001)
By examining technology transfer through concrete case studies, this book offers practical guidance for all those with interest in the field.
Includes bibliographical references.
osc 07/09/2016
Loans
Keywords: Technological Innovation